2022
DOI: 10.3390/jcm11051387
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine for Prevention of Atrial Fibrillation after Cardiac Surgery in the Early Postoperative Period

Abstract: Background. Postoperative atrial fibrillation (POAF) is a common complication of cardiac surgery. It has been proven to be associated with an increase in the incidence of early complications and mortality, an increase in the rate of hospital stay duration, and economic costs of their treatment. One of the pharmaceutical drugs recommended by the American College of Cardiology (ACC)/American Heart Association (AHA) for preventing POAF is colchicine (class IIB). However, the results of research on the efficacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Some clinical studies and meta analyses favor the use of colchicine to prevent postoperative atrial fibrillation (2,14,(22)(23)(24), while others do not (25)(26)(27)(28). In recent years, several new clinical trials on colchicine have been conducted and reported (29)(30)(31). In our study, we focus on the available RCTs to evaluate the efficacy and safety of colchicine in prevention of post-operative AF (2,14,22,23,(25)(26)(27)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical studies and meta analyses favor the use of colchicine to prevent postoperative atrial fibrillation (2,14,(22)(23)(24), while others do not (25)(26)(27)(28). In recent years, several new clinical trials on colchicine have been conducted and reported (29)(30)(31). In our study, we focus on the available RCTs to evaluate the efficacy and safety of colchicine in prevention of post-operative AF (2,14,22,23,(25)(26)(27)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several new clinical trials on colchicine have been conducted and reported (29)(30)(31). In our study, we focus on the available RCTs to evaluate the efficacy and safety of colchicine in prevention of post-operative AF (2,14,22,23,(25)(26)(27)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to assess the variance in POAF rates, we performed a preliminary analysis of our data after randomization of 100 patients. According to the inclusion/exclusion criteria and selected surgical interventions (CABG and/or AVR), at the preliminary stage of the analysis, it was shown that incidence rates of POAF were 18% in the experimental group vs. 29.4% in the control group [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Deftereos et al also showed that colchicine administration, at a dose of 0.5 mg twice daily, for 3 months after pulmonary vein isolation in patients with paroxysmal AF, resulted in a significantly lower rate of AF recurrence over a median of 15 months of follow-up (Deftereos et al, 2014). However, a recent randomized controlled trial (1 mg of colchicine 24 h before the surgery, as well as on days 2, 3, 4, and 5 in the postoperative period) did not detect any statistically significant differences between the control and colchicine groups within 7 days after surgery (Shvartz et al, 2022). Two other studies also found similar results (Bessissow et al, 2018;Tabbalat et al, 2020).…”
Section: Therapeutic Potential Of Targeting Immune Remodelingmentioning
confidence: 97%